1998
DOI: 10.1161/01.cir.97.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Disease Severity, and the Risk of Long-term Cardiac Events in Patients With a Decreased Ejection Fraction After Myocardial Infarction

Abstract: Personality influences the clinical course of patients with a decreased LVEF. Emotional distress in these patients is unrelated to disease severity but reflects individual differences in personality. Clinical trials should take a broad view of the target of intervention; assessment of LVEF and personality may identify patients at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
237
4
17

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 356 publications
(277 citation statements)
references
References 52 publications
19
237
4
17
Order By: Relevance
“…Type D has been associated with increased depressive symptoms in several studies (Denollet & Brutsaert, 1998;Denollet, Pederson, Ong, et al, 2006;Denollet et al, 1996), and has also been shown to be associated with other constructs related to cardiovascular outcomes, such as vital exhaustion (Pedersen & Denollet, 2003;Pedersen & Middel, 2001). Assessment of vital exhaustion and Type D personality in cardiac patients showed that those with a Type D disposition were likely to have a high vital exhaustion score (Pedersen & Middel, 2001).…”
Section: Associations With Depression and Chdmentioning
confidence: 97%
See 3 more Smart Citations
“…Type D has been associated with increased depressive symptoms in several studies (Denollet & Brutsaert, 1998;Denollet, Pederson, Ong, et al, 2006;Denollet et al, 1996), and has also been shown to be associated with other constructs related to cardiovascular outcomes, such as vital exhaustion (Pedersen & Denollet, 2003;Pedersen & Middel, 2001). Assessment of vital exhaustion and Type D personality in cardiac patients showed that those with a Type D disposition were likely to have a high vital exhaustion score (Pedersen & Middel, 2001).…”
Section: Associations With Depression and Chdmentioning
confidence: 97%
“…In studies which measured both depression and Type D, results showed that Type D remained the strongest psychological predictor of outcomes (Denollet & Brutsaert, 1998;Denollet, Pederson, Ong, et al, 2006;Denollet et al, 1996). Depression even became non-significant in some studies (Table 1) (Denollet & Brutsaert, 1998;Denollet, Pederson, Ong, et al, 2006). Social inhibition may in fact be the crucial aspect of risk prediction.…”
Section: Associations With Depression and Chdmentioning
confidence: 99%
See 2 more Smart Citations
“…Ironically, this misunderstanding was stated in an editorial comment [16] on a Type D article whereas in the actual Type D article [22] it was clearly asserted that: "… it is important to examine a broader scope of psychosocial factors than has previously been considered in relation to CHD" [p. 167, italics added]. In the very same article, it was also stated that: "clinical diagnoses of affective disorder, self-report measures of negative emotions and personality test scores may be independent predictors of adverse cardiac events" and furthermore that: "… the most powerful prediction scheme is likely to be one that incorporates both biomedical and psycho-social factors, including specific emotions and global personality traits" [22, p. 172, italics added].…”
mentioning
confidence: 99%